Dukungan koleksi pusat perpustakaan UIN Syarif Hidayatullah Jakarta bagi aktivitas penelitian dosen - Siti Maryam (Pusat Perpustakaan UIN Syarif Hidayatullah Jakarta, 2016)
This article discuses the evaluation of UIN Syarif Hidayatullah Jakarta Library collection.The focus of evaluation is on book collections that have been cited by the lecturers in theirresearch activites. By using citation analysis, the objective of the evaluation is to measurehow the book collection at the Center Library of UIN Jakarta fulfill the information resourcesneeded by the lecturer (researcher) in the university. The population of this evaluation are allof books cited by the UIN Jakarta lecturers in their research report in 2014. The number ofthe population are 4.999 books (titles), and 539 titles of them (more than 10%) were taken assamples. The samples of the book have verified with the UIN Jakarta Center Library Catalog(TULIS) to ensure if the books are avalaible at the collection or not.The findingt of this research is among 539 books title, only 180 title (33%)are avalaible inthe UIN Jakarta Center Library collection. Thus the conclusion of the evaluation is that thecollection of books at UIN Jakarta Center Library are not fully support to the need of researchactivites in 2014.